The Old Modernist Challenge: Navigating the Hypermodern World of Don DeLillo’s White Noise - Andrew Terleckyj (Athens Journal of Humanities & Arts, 2023)
While many critics believe technology and media create a postmodern world of endless simulacrum, fractured identity, and vanishing boundaries in White Noise, this essay explores the possibility that DeLillo’s text in fact reveals the hypermodernist world of Paul Virilio, resisting these apocalyptic consequences of technology. Daniel Joseph Singal’s definition of Modernism helps to show how central aims of the Modernist project – that is, to achieve authenticity and reintegrate Victorian dichotomies – are not only possible but also imperative to achieve in White Noise, for the text implicitly suggests that rejecting Modernist principles may result in a national, epistemic crisis. More specifically, the novel points to one particular stream of Modernist culture as the antidote to epistemic failure. This stream, which Singal attributes to John Dewey, inspirits the novel’s central Modernist characters: Jack and Denise Gladney. Using Modernist ideologies, these two characters successfully find authenticity and meaning in a growingly complex technological world.